Meningkatkan Kompetensi Guru dalam Penyusunan Proposal Penelitian Tindakan Kelas (PTK) Melalui Bimbingan Kelompok Berbasis MGMP - Ridwan, Ridwan (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2016)
Background of this research was there are many teachers at SMK Negeri 9 Mataram didn’t want conduct Classroom Action Research (CAR) yet, it caused by learning burden so it had impact on low motivation in writing article, the best solution was researcher conducted guiding as group. This research aimed to know how far effectiveness of implementing group guiding in effort to improve teachers’ competence at SMK Negeri 9 Mataram in arranging lesson CAR proposal which has benefit for teachers in improving teachers professionalism in daily duty. In implementing School Action Research (SAR) was two cycles, where every cycle had four stages namely planning, acting, observing, and reflecting. Ijndicator of completeness in this research was PKN teachers’ competence: if > 10 % from amount of participant which got mean score ≥ 85,00. Result of School Action Research (SAR) in cycle II was gotten data such as; 1) observation of supervisor (4,22), 2) observation of teachers (4,11), 3) result of classical work (88,29). Indicator of completeness had reached, School Action Research (SAR) was success, and research was stopped in cycle II. Group counseling was very effective in effort to improve PKn teachers’ competence in arranging CAR proposal because 90% from amount of participant was 47 (fourty seven) teachers had been succeeded arranged CAR proposal based on their wish. It suggested for headmaster to conduct guiding activities for teachers it became their responsibility in effort to improve competence in sustainable profession development (PKB) activities.